l-Arginine-Dependent Epigenetic Regulation of Interleukin-10, but Not Transforming Growth Factor-β, Production by Neonatal Regulatory T Lymphocytes - Yu, Hong-Ren; Tsai, Ching-Chang; Chang, Ling-Sai; Huang, Hsin-Chun; Cheng, Hsin-Hsin; Wang, Jiu-Yao; Sheen, Jiunn-Ming; Kuo, Ho-Chang; Hsieh, Kai-Sheng; Huang, Ying-Hsien; Yang, Kuender D.; Hsu, Te-Yao (Frontiers in Immunology, 2017)
A growing number of diseases in humans, including trauma, certain cancers, and infection, are known to be associated with L-arginine deﬁciency. In addition, L-arginine must be supplemented by diet during pregnancy to aid fetal development. In conditions of L-arginine depletion, T cell proliferation is impaired. We have previously shown that neonatal blood has lower L-arginine levels than adult blood, which is associated with poor neonatal lymphocyte proliferation, and that L-arginine enhances neonatal lymphocyte proliferation through an IL-2-independent pathway. In this study, we have further investigated how exogenous L-arginine enhances neonatal regulatory T-cells (Tregs) function in relation to IL-10 production under epigenetic regulation. Results showed that cord blood mononuclear cells (CBMCs) produced higher levels of IL-10 than adult peripheral blood mononuclear cells (PBMCs) by PHA stimulation but not by anti-CD3/anti-CD28 stimulation. Addition of exogenous L-arginine had no effect on TGF-b production by PBMCs or CBMCs, but enhanced IL-10 production by neonatal CD4+CD25+FoxP3+ Tregs. Further studies showed that IL-10 promoter DNA hypomethylation, rather than histone modification corresponded to the L-arginine-induced increase in IL-10 production by neonatal CD4+ T cells. These results suggest that L-arginine modulates neonatal Tregs through the regulation of IL-10 promoter DNA methylation. L-arginine supplementation may correct the Treg function in newborns with L-arginine deficiency.